AI Smart Table - Panes, Jessa Mae; Gonzaga, Josephine (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated an AI Smart Table with a Dry Ingredients Dispenser designed to improve efficiency, accuracy, organization, and hands-free operation during pastry preparation for home bakers and local cake shops. Guided by Rogers’ Diffusion of Innovations Theory, the study employed a project-based research design combined with a quantitative approach. The prototype was fabricated using stainless steel and integrated an AI voice recognition module, automated dispensing mechanism, storage compartments, and mobility features. Its performance was evaluated by fifteen (15) purposively selected home bakers and local cake shop owners from the Association of Kidapawan Hotels, Resorts, and Restaurants (AKHoRR) in Kidapawan City using a researcher-made, expert-validated questionnaire. Data were analyzed using frequency count and mode. Results showed that the AI Smart Table was successfully developed and demonstrated excellent voice detection performance under varying distances, environmental conditions, and users. The dispensing mechanism consistently delivered accurate measurements with only minimal acceptable variations, while the system achieved a highly acceptable level of safety and usability. Although slight inconsistencies were observed in dispensing smaller ingredient quantities, the prototype proved to be functional, reliable, practical, and suitable for household and small-scale baking applications. The study recommends improving the calibration of the dispensing mechanism, incorporating more advanced sensors and voice recognition capabilities, increasing the number of respondents in future evaluations, and exploring additional automation features to further enhance system performance. The study supports Sustainable Development Goal (SDG) 9: Industry, Innovation and Infrastructure by promoting innovation in food preparation technology and SDG 8: Decent Work and Economic Growth by improving productivity and operational efficiency for small-scale baking enterprises. Furthermore, the developed system contributes to technological and economic sustainability by encouraging the adoption of intelligent automation that enhances precision, reduces manual effort, and supports innovation in modern kitchen operations.
Keywords: AI Smart Table; Arduino Nano; Dry Ingredients Dispenser; Pastry Preparation; Voice Recognition; Workstation Design